2015
DOI: 10.1002/ece3.1482
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of pattern camouflage strategies in waterfowl and game birds

Abstract: Visual patterns are common in animals. A broad survey of the literature has revealed that different patterns have distinct functions. Irregular patterns (e.g., stipples) typically function in static camouflage, whereas regular patterns (e.g., stripes) have a dual function in both motion camouflage and communication. Moreover, irregular and regular patterns located on different body regions (“bimodal” patterning) can provide an effective compromise between camouflage and communication and/or enhanced concealmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
(233 reference statements)
0
13
0
Order By: Relevance
“…First, it could be due to the coarse scale at which we investigated the association between habitat and plumage patterns. Many of the empirical studies that demonstrate a camouflage function of patterns in non-colour changing animals show an association in one or a limited number of species (e.g., Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Wilson-Aggarwal et al, 2016) or were found via predator–prey computer simulations (e.g., Stevens, Yule & Ruxton, 2008; Stevens et al, 2011; Scott-Samuel et al, 2011; Troscianko et al, 2013; How & Zanker, 2014; Hughes, Troscianko & Stevens, 2014; reviewed in Marshall & Gluckman, 2015). At the level of microhabitats, some studies demonstrate that individual behaviours may facilitate camouflage, such as a behavioural choice to rest on backgrounds that enhance camouflage (Tsurui, Honma & Nishida, 2010; Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Troscianko et al, 2016; Wilson-Aggarwal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, it could be due to the coarse scale at which we investigated the association between habitat and plumage patterns. Many of the empirical studies that demonstrate a camouflage function of patterns in non-colour changing animals show an association in one or a limited number of species (e.g., Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Wilson-Aggarwal et al, 2016) or were found via predator–prey computer simulations (e.g., Stevens, Yule & Ruxton, 2008; Stevens et al, 2011; Scott-Samuel et al, 2011; Troscianko et al, 2013; How & Zanker, 2014; Hughes, Troscianko & Stevens, 2014; reviewed in Marshall & Gluckman, 2015). At the level of microhabitats, some studies demonstrate that individual behaviours may facilitate camouflage, such as a behavioural choice to rest on backgrounds that enhance camouflage (Tsurui, Honma & Nishida, 2010; Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Troscianko et al, 2016; Wilson-Aggarwal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, irregular patterns (mottled) tend to function in stationary camouflage while those that regularly repeat a pattern or motif (bars, spots) function in motion camouflage, which are in turn predicted to be more effective in closed and open habitats, respectively (Marshall & Gluckman, 2015). Birds are the most well described taxonomic group of animal and can be found in all types of habitats on all major landmasses (Gluckman & Cardoso, 2010; Jetz et al, 2012), making them particularly well suited for investigating sensory ecology hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crucially, visual modelling studies have shown that such local adaptation can prevent detection by the actual visual systems of predators, such as hunting birds (e.g. Marshall et al, 2015), thus indicating that camouflage tends to be optimised to local habitats under natural selection.…”
Section: Introductionmentioning
confidence: 99%